2016
DOI: 10.1111/ceo.12764
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary retinal nerve fibre layer thickness and its association with refractive error in Chinese children: the Anyang Childhood Eye Study

Abstract: Retinal nerve fibre layer thickness decreased with increasing AL, higher myopia, bigger cup area, smaller disc and rim area, and a smaller nerve head volume, but the coefficient of determination for all these associations was small. The RNFL in myopes was significantly thinner than emmetropes or hyperopes, but with small absolute differences. The study provides RNFL values for healthy 7-year-old Chinese children. Follow up of this cohort to observe the change of RNFL thickness with myopia and possible change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 51 publications
(56 reference statements)
4
28
0
Order By: Relevance
“…RNFL thickness and its variation among normal children has previously been reported in OCT studies [4,6,17,18]. In our study, the range of the RNFL thickness was narrowest for the average RNFL (about 50 µm), being wider in the quadrants (▶ Table 1).…”
Section: Octsupporting
confidence: 75%
“…RNFL thickness and its variation among normal children has previously been reported in OCT studies [4,6,17,18]. In our study, the range of the RNFL thickness was narrowest for the average RNFL (about 50 µm), being wider in the quadrants (▶ Table 1).…”
Section: Octsupporting
confidence: 75%
“…In the present study, axial length (AL) was not measured; however, AL has minimal influence on macular and peripapillary retinal nerve fibre layer measurements . Other authors showed an influence of AL on OCT measurements and reported that correlations with SE are inverse to those found with AL, as AL increased with decreasing SE . Al Haddad et al also reported a negative correlation between SE and AL in healthy children ( P < 0.001) and assessed the influence of SE on all parameters …”
Section: Discussionmentioning
confidence: 52%
“…17,18 Other authors showed an influence of AL on OCT measurements and reported that correlations with SE are inverse to those found with AL, as AL increased with decreasing SE. 19,20 Al Haddad et al also reported a negative correlation between SE and AL in healthy children (P < 0.001) and assessed the influence of SE on all parameters. 21 Realini et al suggested that the process for developing imaging reference databases could be improved by standardising eligibility requirements and data collection protocols.…”
Section: Discussionmentioning
confidence: 98%
“…To date, only age 7,8 , refraction 9 or axial length (AL) 10 have been consistently associated with measured pRNFLT across studies. In addition, the majority of large-scale studies assessing these associations were performed in (young) Asian populations 6,[11][12][13][14] . It is unclear whether or not these results can be applied to European, i.e.…”
Section: While Prnflt Measurements Have Increased Insight Into the Dementioning
confidence: 99%